Metabolic assessment and enteral tube feeding usage in children with acute neurological diseases - Leite, Heitor Pons; Fantozzi, Gina (São Paulo Medical Journal, 1998)
OBJECTIVE: To report on acquired experience of metabolic support for children with acute neurological diseases, emphasizing enteral tube feeding usage and metabolic assessment, and also to recommend policies aimed towards improving its implementation. DESIGN: Retrospective analysis. SETTING: Pediatric Intensive Care Unit of Hospital do Servidor Público Estadual de São Paulo. SUBJECTS: 44 patients consecutively admitted to the Pediatric ICU over a period of 3 years who were given nutrition and metabolic support for at least 72 hours. Head trauma, CNS infections and craniotomy post-operative period following tumor exeresis were the main diagnoses. MEASUREMENTS: Records of protein-energy intake, nutrient supply route, nitrogen balance and length of therapy. RESULTS: From a total of 527 days of therapy, single parenteral nutrition was utilized for 34.3% and single enteral tube feeding for 79.1% of that period. 61.4% of the children were fed exclusively via enteral tube feeding, 9.1% via parenteral and 39.5 % by both routes. The enteral tube feeding was introduced upon admission and transpyloric placement was successful in 90% of the cases. Feeding was started 48 hours after ICU admission. The caloric goal was achieved on the 7th day after admission, and thereafter parenteral nutrition was interrupted. The maximum energy supply was 104.2 ± 23.15 kcal/kg. The median length of therapy was 11 days (range 4-38). None of the patients on tube feeding developed GI tract bleeding, pneumonia or bronchoaspiration episodes and, of the 4 patients who were given exclusive TPN, 2 developed peptic ulcer. The initial urinary urea nitrogen was 7.11 g/m2 and at discharge 6.44 g/m2. The protein supply increased from 1.49 g/kg to 3.65 g/kg (p< 0.01). The nitrogen balance increased from -7.05 to 2.2 g (p< 0.01). CONCLUSIONS: Children with acute neurological diseases are hypercatabolic and have high urinary nitrogen losses. The initial negative nitrogen balance can be increased by more aggressive feeding regimes than the usual ones. Early tube feeding was well tolerated, which permits the conclusion that it is a safe and effective method for nutrition support. Recommendations of basic rules for metabolic support are made.